2017
DOI: 10.1080/17512433.2017.1347502
|View full text |Cite
|
Sign up to set email alerts
|

Potential benefits of zolpidem in disorders of consciousness

Abstract: It has been suggested that zolpidem may arouse patients with decreased level of consciousness. Zolpidem may partially or even completely reverse abnormal cell metabolism following brain damage. In this article, available evidences regarding effects of zolpidem on disorders of consciousness were reviewed. Areas covered: A literature review was conducted using PubMed, Scopus, Medline, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews and Google Scholar as online databases. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Third, we consider the possibility that cortical connectivity, network topology and complexity are true biomarkers of the conscious state, indicating that the level of consciousness of the case examples presented in this paper improved upon exposure to anesthesia. This explanation is supported by previous studies that have shown that a sedative GABAergic drug – zolpidem – can increase arousal in patients with DOC ( Du et al, 2014 ; Machado et al, 2014 ; Noormandi et al, 2017 ; Sripad et al, 2020 ). These observations can be reconciled using the hypothesis that consciousness relies on brain networks which are tuned to criticality, a narrow window between stability and chaos; disorder and order ( Tagliazucchi, 2017 ; Popiel et al, 2020 ; Toker et al, 2022 ).…”
Section: Discussionsupporting
confidence: 78%
“…Third, we consider the possibility that cortical connectivity, network topology and complexity are true biomarkers of the conscious state, indicating that the level of consciousness of the case examples presented in this paper improved upon exposure to anesthesia. This explanation is supported by previous studies that have shown that a sedative GABAergic drug – zolpidem – can increase arousal in patients with DOC ( Du et al, 2014 ; Machado et al, 2014 ; Noormandi et al, 2017 ; Sripad et al, 2020 ). These observations can be reconciled using the hypothesis that consciousness relies on brain networks which are tuned to criticality, a narrow window between stability and chaos; disorder and order ( Tagliazucchi, 2017 ; Popiel et al, 2020 ; Toker et al, 2022 ).…”
Section: Discussionsupporting
confidence: 78%
“…It has been reported that zolpidem has positive effects in several conditions involving decreased level of consciousness, but no benefits of zolpidem were detected in patients with disorders of consciousness. 31 Deep brain stimulation shows therapeutic efficacy in improving the consciousness of patients with disorders of consciousness who show somatosensory evoked potentials and brainstem auditory evoked potentials in at least one side. 32 A previous study 33 reported that transcranial direct current stimulation improved behavior in 43% of patients with a minimally consciousness state.…”
Section: Discussionmentioning
confidence: 99%
“…The use of neurostimulants in the management of patients with DOC is still controversial, and the existing studies are focused more on the role of agents that have a “direct” effect on recovery of consciousness, like Amantadine (a synthetic tricyclic amine with antiviral, antiparkinsonian, and antihyperalgesic activities) or Zolpidem (a benzodiazepine receptor agonist that is used for the treatment of insomnia; see for example [ 67 , 68 , 69 , 70 ]), leaving aside analysis on their potential effects on sleep disorders [ 71 ]. ITB is, instead, mainly used as a central action treatment to improve spasticity, even in patients with DOC, and few uncontrolled studies and case reports have suggested ITB has a potential role in stimulating recovery of consciousness [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%